The effect of workload on work stress of nurses in hospital - Prasanti Adriani; Noor Yunida Triana; Rani Prabandari (Universitas 'Aisyiyah Yogyakarta, 2022)
The nursing profession is a stressful job and prone to stress due to the complexity of job demands and needs, high expectations, many responsibilities, and limited authority. The purpose of this study is to determine the relationship between workload and the work stress of nurses at the Ajibarang Regional General Hospital, Banyumas Regency in 2021. This research is an analytical survey using a cross-sectional approach. The sampling technique used in this study was a total sample of 68 respondents. Data analysis was carried out using the Chi-square test. The majority of respondents were female (60.2%). The workload of nurses was the most in the heavy category (67.6%) while the work stress of the majority of respondents was in the moderate category (61.8%). The results of this study showed a relationship between workload and the incidence of work stress in nurses by a p-value of 0.000 (a= 0.05%). Hospital management is obliged to ensure a balance between the needs of patients and the number and competence of nurses. This is to avoid work stress on nurses in order to improve the quality of service and patient safety.